What Will Come After V‐NAND—Vertical Resistive Switching Memory?. (28th February 2019) - Yoon, Kyung Jean; Kim, Yumin; Hwang, Cheol Seong
Abstract: The NAND flash memory serves as the key enabler of the flourishing of portable handheld information devices, such as the cellular phone. The recent upsurge in the sales of vertical NAND flash memory (V‐NAND) entails a further increase in the available information capacity at the edge devices and the servers with higher performance and lower power consumption compared with the magnetic hard‐disc drives. Nonetheless, there will certainly be an upper limit for the number of stacked layers, which will be the point at which further memory density increase will stop. While V‐NAND is a supreme outcome of semiconductor memory technologies, it still relies on conventional Si‐based materials. The newly explored memory materials and concepts, such as the resistance‐based memories, can therefore be an appealing contender to or successor of V‐NAND. In this review, the current state of V‐NAND is first briefly looked into, and then the eventual limitation of memory density increase and performance boost are discussed. Most importantly, the possible strategies of integrating the resistance‐based memories into the vertical architecture are then discussed. Finally, the outlook for such resistance‐based vertical memories is presented. Abstract : Pathways to overcome the scaling limitation of vertical NAND flash memory (V‐NAND), the present market leading nonvolatile memory, providing new materials and array structure suggestions, are provided. Specifically, the favorable aspects of a vertical resistive random access memory (V‐ReRAM) structure, such as areal density and decoding schemes, are highlighted in comparison with the commercialized nonvolatile memories: 3D‐Crosspoint and V‐NAND.